An Examination of Motivations, Attitudes and Charitable Intentions for Running in a Charity Event - Gomez, Edwin; Hill, Eddie; Ridinger, Lynn; Shiparo, Stephen (Journal of Amateur Sport, 2022)
Running, as a form of leisure time physical activity is generally popular due to its low-cost entry, easy access to practice, and the convenience and accessible nature of the activity. Specifically, one type of running experience sought by many is charitable running or running for a cause (i.e., cause-related sport event). While there is a growing body of literature on charity sport events, little is known about how the charitable motives and participant identity with the event affect future behaviors associated with the cause and the event. Grounded in identity theory, the purpose of this article was to examine the effect of salient identities and charitable motives on future intentions associated with a cause-related event. Data were collected from the second annual Norfolk Freedom Half Marathon, in Virginia, via an online survey that was sent to all registered runners (1,372) one week after the race and 557 participants responded. We found charity motives to be the dominant influence on both charitable and purchase intentions in cause-event participants. This study contributes to the existing amateur sport literature as one of the first to report on a military-oriented sport event with military affiliated participants; the creation of the Charitable Motives in Sport Scale (CMISS), the Runner Identity Scale (RIS) and the Military Identity Scale (MIS); and the addition of a new military/runner identity typology, which we hope would be useful for future military-affiliated running events.